2011
DOI: 10.1007/s00115-011-3324-5
|View full text |Cite
|
Sign up to set email alerts
|

Immunadsorption bei steroidrefraktärem Schub der Multiplen Sklerose

Abstract: Immunoadsorption for the treatment of steroid-unresponsive MS relapses was safe and effective. The response rate was comparable to published results with PE. With IA, in contrast to unselective PE, administration of human plasma products is not necessary, avoiding associated risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
9

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 24 publications
1
21
0
9
Order By: Relevance
“…One patient gradually improved but deteriorated again along with the development of jugular venous thrombosis, and two patients did not respond at all. The response to IA seems to be comparable to the best results achieved in PE series [5,6] and to two very recent retrospective analyses of the effect of IA in steroid-refractory MS cases [18,19]. As in our own PE study [10], significant clinical improvement was seen after the third extracorporeal treatment session with a trend in favor of early IA initiation compared to delayed IA initiation.…”
Section: Discussionsupporting
confidence: 86%
“…One patient gradually improved but deteriorated again along with the development of jugular venous thrombosis, and two patients did not respond at all. The response to IA seems to be comparable to the best results achieved in PE series [5,6] and to two very recent retrospective analyses of the effect of IA in steroid-refractory MS cases [18,19]. As in our own PE study [10], significant clinical improvement was seen after the third extracorporeal treatment session with a trend in favor of early IA initiation compared to delayed IA initiation.…”
Section: Discussionsupporting
confidence: 86%
“…Two randomized sham-controlled studies have shown a beneficial effect of plasma exchange (PE) in adult patients with acute CNS demyelinating diseases failing to respond to treatment with ACTH or high-dose corticosteroids, respectively [2,3]. Additionally, one uncontrolled prospective study [4] and several case series [5,6] have shown comparable effects of immunoadsorption (IA) in such cases. The International Pediatric Multiple Sclerosis (MS) Study Group states: ‘Children with severe relapses not improving after high-dose IVMP pulse or with contraindications to glucocorticosteroids might benefit from a treatment with plasma exchange' [7].…”
Section: Introductionmentioning
confidence: 99%
“…Die bisher publizierten Erfahrungen zur IA wurden mit der Tryptophan-IA gesammelt und zeigten einheitlich eine ebenso gute Wirksamkeit wie der PA (Abb. 1) [15,16,17,18,19]. Ein wirksames Behandlungsschema für den MS-Schub scheinen 5-6 Behandlungen mit je 2-2,5 l behandeltem Plasmavolumen zu sein.…”
Section: Multiple Skleroseunclassified
“…Patienten mit einer Beteiligung des Nervus opticus und einem beeinträchtigten Sehvermögen zeigten hierbei besonders beeindruckende Ergebnisse (Abb. 2) [16,17,18]. Auch pädiatrische Patienten konnten erfolgreich behandelt werden [20].…”
Section: Multiple Skleroseunclassified